KARAKTERISTIK DAN KERAGAMAN TANAH KETAPING SELATAN KECAMATAN BATANG ANAI KABUPATEN PADANG PARIAMAN - Adrinal Adrinal; Neldi Armon (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2010)
A study of soil characteristics and soil variation was carried out in Ketaping Selatan, Batang Anai, Padang Pariaman District. The study aimed to identify the characteristics and variation of soil of Ketaping Selatan as a selected village under University of Andalas supervisory. The results indicated that Ketaping Selatan has two soil variations namely Typic Udifluvents and Terric haplosaprists. Both soils are categorized as soils with low fertility and low carrying capacity. It is needed a proper management for enhanching their soil productivity, erspecially for agricultural purposes. Keyword : soil caracteristics, soil variation